INNOVATION AS AN ELEMENT OF THE DEVELOPMENT OF HEALTHCARE AND EDUCATION IN ISRAEL - Рошка, Петр; Дрейхер, Далия; Исраель, Мiлана; Благоразумна, О.М. (Modern engineering and innovative technologies, 2022)
In a rapidly changing world, new needs are constantly emerging. Changes in different areas of life affect all areas of human activity. Israel's health and education systems are no exception. One of the possible ways of their development is innovation. The